Evaluation method and device for metal pole plate coating of fuel cell
By conducting coating acceleration experiments on the metal plate coating of fuel cell, simulating the harsh working environment of fuel cell and evaluating the durability of the coating, the problem of difficult to quickly and effectively evaluate the durability of the coating in the prior art is solved, and the problem of rapid and effective evaluation of the durability of the coating is achieved. Efficient and accurate durability evaluation.
Patent Information
- Application Number
- CN202411695122.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to quickly and effectively evaluate the durability of fuel cell metal plate coatings in harsh working environments, especially the lack of research on the effect of vibration on coating bonding and hydrophilicity.
The coating acceleration experimental method is used to simulate the working condition test of temperature and potential cycles in the electrolyte under ultrasonic conditions. By comparing the initial and final performance information, the binding force, contact resistance, corrosion current density and contact of the coating are evaluated. horn.
It realizes the actual working conditions of the entire life of fuel cells quickly and efficiently in the laboratory in a short period of time, comprehensively evaluates the durability of metal plate coatings, improves evaluation efficiency and accuracy, and reduces R&D costs.
Smart Images

Figure CN119395267A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a method and a device for evaluating a metal plate coating of a fuel cell. Background Art
[0002] With the rapid development of hydrogen energy, the requirements for the power density of proton exchange membrane fuel cells (PEMFC) are becoming higher and higher. Metal plates have better electrical, thermal and mechanical properties, which makes the plate material used in fuel cells gradually transition from graphite plates to metal plates.
[0003] Metal plates and their coatings are easily affected by multiple factors such as pH, temperature, and potential, which are related to the working environment and working conditions. The working environment of PEMFC is harsh: high humidity, high potential, and uneven temperature distribution. At the same time, the working conditions of PEMFC are complex, and vibration is prone to occur in actual road driving vehicle applications. Metal plates and their coatings have the disadvantages of being easily corroded and easily detached under the above PEMFC working environment, which has an adverse effect on the durability of PEMFC. It is crucial to quickly evaluate the durability of metal plates and their coatings under the working environment and working conditions of fuel cells.
[0004] The current existing technology for durability testing of metal plates and their coatings only examines the effects of pH, temperature, potential, etc. on durability, but does not study the effect of vibration on coating performance. In fact, the vibration process is a key factor affecting the adhesion of the coating; and the current technology only explores the effect of simulated working conditions on the conductivity and corrosion resistance of the coating, and does not study the effect on the adhesion and hydrophilicity of the coating.
[0005] Therefore, in view of the above technical problems, it is necessary to provide a method and device for evaluating the metal plate coating of a fuel cell.
[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0007] The purpose of the present invention is to provide a method and device for evaluating the coating of a fuel cell metal plate.
[0008] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0009] Evaluation method for fuel cell metal plate coating,
[0010] Preparing metal plate samples with coatings and collecting initial performance information of the samples;
[0011] After the sample has undergone accelerated coating testing, the final performance information of the sample is collected;
[0012] The final performance information is compared with the initial performance information to at least evaluate the performance of the sample, wherein the performance of the sample is selected from the group consisting of: bonding strength, contact resistance, corrosion current density, and contact angle.
[0013] In one or more embodiments of the present invention, the coating acceleration experiment is: in an electrolyte under ultrasonic conditions, the metal electrode plate sample is subjected to a simulated operating condition test of temperature cycling and potential cycling.
[0014] In one or more embodiments of the present invention, the frequency of the ultrasonic condition is 30KHZ-100KHZ. Low-frequency sound waves are advantageously used here, and the low-frequency sound waves have longer wavelengths and stronger penetrating power, so that they can penetrate into the metal plate coating to reach the base layer to test the bonding strength.
[0015] In one or more embodiments of the present invention, the electrolyte is an acidic aqueous solution with a pH value of 3 to 5, in which a fluorine source with a mass concentration of 0.01 to 100 ppm and a mixture of H2O2 with a mass concentration of 0.01 to 100 ppm are added, and hydrogen or oxygen is passed through the electrolyte. Preferably, the electrolyte is a mixture of HF with a mass concentration of 0.01 to 100 ppm and H2O2 with a mass concentration of 0.01 to 100 ppm added to an H2SO4 aqueous solution with a pH value of 3 to 5, and hydrogen or oxygen is passed through the electrolyte. The acid source of the acidic aqueous solution is H2SO4, hydrochloric acid, phosphoric acid, water-soluble dihydrogen phosphate (such as alkali metal salts such as sodium potassium), water-soluble hydrogen sulfate (such as alkali metal salts such as sodium potassium), etc., as long as it satisfies the requirements of providing an acidic environment for this solution. Preferably, the amount of hydrogen or oxygen passed into the electrolyte is 50-100 sccm.
[0016] In one or more embodiments of the present invention, the fluorine source is a fluorine-containing substance that is used to dissociate in an acidic aqueous solution to form free fluorine. The fluorine-containing substance can be a fluorine-containing substance that can provide fluoride ions in an aqueous solution state, such as HF, NaF, potassium fluoride, etc.
[0017] In one or more embodiments of the present invention, the coating is selected from a non-metallic coating, a metal-based coating, and a composite coating.
[0018] In one or more embodiments of the present invention, the simulated operating condition test includes: performing a constant potential polarization test at a potential of 0.8 V for 6-12 hours at a temperature range of -30°C-60°C, performing a constant potential polarization test at a potential of 1.6 V for 3-6 hours at a temperature range of -30°C-60°C, performing a constant potential polarization test at a potential of 0.8 V for 12-24 hours at a temperature range of 60°C-90°C, and performing a constant potential polarization test at a potential of 1.6 V for 3-6 hours at a temperature range of 60°C-90°C.
[0019] In one or more embodiments of the present invention, the frequencies of ultrasonic conditions in different sections in the simulated operating condition test are different or the same.
[0020] In one or more embodiments of the present invention, an evaluation device is used to perform an evaluation method for a fuel cell metal plate coating.
[0021] In one or more embodiments of the present invention, the evaluation device at least includes an electrolytic cell for containing electrolyte for testing and a functional device attached to the electrolytic cell. The functional device may be associated with the electrolytic cell or external (here, associated with the electrolytic cell means that the functional device is built into the evaluation device, and external means that the corresponding functional device is not built into the evaluation device, but is an external device added during the detection). The functional device is selected from: a power supply device, a temperature control device, and an ultrasonic device.
[0022] Compared with the prior art, the fuel cell metal plate coating evaluation method and device of the present invention optimizes the fuel cell durability evaluation conditions and methods, thereby achieving a rapid and efficient simulation of the actual working conditions of the fuel cell's entire life cycle in a laboratory environment in a short period of time, thereby achieving a comprehensive evaluation of the durability of the fuel cell metal plate coating in a short period of time, and improving the evaluation efficiency and accuracy of the coating performance; using an ultrasonic pool, based on the actual vehicle operating conditions of the fuel cell, compiling vibration conditions similar to it, controlling the ultrasonic frequency, PH, temperature cycle, and potential cycle condition parameters to simulate the actual working conditions of the fuel cell for experiments, having high effectiveness, and being able to quickly and accurately evaluate the stability of the metal plate coating material in the early stage of research and development, thereby reducing the research and development cost of in-situ testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 It is a schematic flow chart of a method for evaluating a fuel cell metal plate coating in one embodiment of the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] It should be noted that the coating of the present invention is not limited to a layer structure obtained by a coating process, but may also include a layer structure formed by processes such as electroplating and magnetron sputtering.
[0027] One object of the present invention is to provide a durability evaluation method for fuel cell metal plate coatings, which can comprehensively evaluate the durability of fuel cell metal plate coatings by testing the initial performance of the metal plate, including mechanical properties, corrosion resistance, conductivity, and hydrophilicity and hydrophobicity, then simulating the actual working conditions of the fuel cell, and finally testing the final performance of the metal plate.
[0028] To achieve the above objectives, specifically in one or more embodiments of the present invention, a durability evaluation method for a fuel cell metal plate coating may include the following steps:
[0029] (1) Testing of initial coating performance: Cut the coated electrode into the required size, clean the surface with solvents such as ethanol or acetone, and test the initial bonding strength, contact resistance, corrosion current density and contact angle of the coating sample;
[0030] (2) Accelerated durability test of coating: An electrochemical three-electrode test system with an electrochemical workstation is used to place the electrolyte pool containing the coated electrode plates into an ultrasonic pool. The ultrasonic frequency, pH, temperature cycle, potential cycle conditions and other parameters are controlled to simulate the actual working conditions of the fuel cell for the experiment.
[0031] (3) Testing of coating final performance: Testing the coating samples for final adhesion, contact resistance, corrosion current density and contact angle.
[0032] (4) Determination of coating durability: The stability of the coating is determined based on the degree of change between the initial and final performance of the coating before and after the accelerated durability test.
[0033] As a preferred embodiment, the coating in step (1) includes: non-metallic coatings such as graphite coatings, conductive polymer coatings and amorphous carbon coatings, etc.; metal-based coatings such as precious metal coatings, metal carbide coatings, metal nitride coatings, metal oxide coatings and alloy coatings, etc.; and composite coatings and other common coatings in the art. The coating processing method can be magnetron sputtering, plasma enhanced atomic layer deposition, ion plating, electrochemical deposition, vapor deposition, heat treatment, ion implantation and spraying.
[0034] As a preferred embodiment, the coating samples in steps (1) and (3) are flat plate samples or bipolar plate samples or monopolar plate samples with flow field structures.
[0035] As a preferred embodiment, the test of the bonding strength in steps (1) and (3) is performed by an indentation method or a scratch method.
[0036] As a preferred solution, the contact resistance test in steps (1) and (3) is performed using a contact resistance tester, and the test pressure range is 0 to 2.0 MPa. A pressure range can be selected for testing to obtain a contact resistance linear curve, or one or several pressure test points can be fixed for comparison.
[0037] As a preferred embodiment, the corrosion current density in steps (1) and (3) is tested by electrochemical polarization testing using an electrochemical three-electrode testing system.
[0038] As a preferred embodiment, the contact angle in steps (1) and (3) is tested using a contact angle meter.
[0039] As a preferred embodiment, the electrochemical three-electrode test system in step (2) comprises an electrochemical workstation, a working electrode consisting of a metal electrode plate coated with a coating, an auxiliary electrode consisting of a platinum sheet, and a reference electrode consisting of Hg / HgSO4.
[0040] As a preferred embodiment, the electrolyte in step (2) refers to a mixture of HF with a mass concentration of 0.01 to 100 ppm and H2O2 with a mass concentration of 0.01 to 100 ppm added to an H2SO4 aqueous solution with a pH value of 3 to 5, and hydrogen or oxygen is passed through the electrolyte; the electrolyte cell material is a corrosion-resistant material such as glass or plastic.
[0041] As a preferred embodiment, the ultrasonic frequency in step (2) is 30KHZ-100KHZ; the medium used in the ultrasonic pool can be at least one of clean water, alcohol and acetone.
[0042] As a preferred embodiment, the electrolytic cell of the electrochemical three-electrode test system in step (2) is arranged inside the ultrasonic pool, the ultrasonic pool has a temperature control system, which can achieve temperature control of -30°C to 90°C, the electrochemical three-electrode test system is connected to the electrochemical workstation, and the electrochemical three-electrode test system has a gas filling system, which can introduce hydrogen or oxygen into the electrolytic cell.
[0043] Example 1
[0044] (1) Testing of initial coating performance: Cut the sample with precious metal coating, here taking gold-plated metal bipolar plate as an example, into 5x5cm 2 Samples AD of different sizes were placed in a beaker and ultrasonically cleaned for 5 minutes with ethanol to remove dust, impurities and oil stains on the coating surface. Sample A was taken and the bonding force between the precious metal coating and the metal substrate in sample A was measured by a scratch tester WS-2005 (the same below) to be 54N. Sample B was taken and the contact resistance of the coating was measured by a contact resistance tester at a test pressure of 0.6MPa to be 0.55mΩcm 2 Sample C was taken, clamped with an electrode clamp and placed in a glass electrolytic cell as the working electrode, and a platinum sheet was used as the auxiliary electrode, and Hg / HgSO4 was used as the reference electrode to form an electrochemical three-electrode test system. The electrolyte was a mixture of HF with a mass concentration of 100 ppm and H2O2 with a mass concentration of 10 ppm added to an H2SO4 aqueous solution with a pH value of 3, and 50 sccm of hydrogen was passed through; the corrosion current density of the sample measured by the electrochemical workstation at a constant potential of 0.84 V (vs. SHE) was 0.08 μA cm -2 Sample D was taken and the contact angle was measured by a contact angle meter to be 85°.
[0045] (2) Accelerated durability test of coating: Another sample with precious metal coating prepared in the previous step was cut into 5x5cm 2 The samples EH of different sizes were placed in a beaker, and ethanol was added for ultrasonic cleaning for 5 minutes to remove dust, impurities and oil stains on the coating surface. Then, an electrochemical three-electrode test system with an electrochemical workstation was used to place the electrolyte pools (the electrolyte was the same as the previous step) containing the plate samples EH with coatings respectively into the ultrasonic pool, and the ultrasonic frequency was set to 30KHZ. The constant potential polarization test was performed at a temperature of 20°C and a potential of 0.8V for 12 hours, at a temperature range of 20°C and a potential of 1.6V for 3 hours, at a temperature range of 90°C and a potential of 0.8V for 12 hours, and at a temperature range of 90°C and a potential of 1.6V for 3 hours.
[0046] (3) Testing of coating performance at the end of the coating period (tested under the same conditions): Sample E was taken and the bonding force between the precious metal coating and the metal substrate in sample E was measured by a scratch tester to be 48 N. Sample F was taken and the contact resistance of the coating was measured by a contact resistance tester under a test pressure of 0.6 MPa to be 1.75 mΩ cm 2 Take sample G, clamp it with an electrode clamp and put it into a glass electrolytic cell as the working electrode, use a platinum sheet as the auxiliary electrode, and Hg / HgSO4 as the reference electrode to form an electrochemical three-electrode test system. The electrolyte is a mixture of HF with a mass concentration of 100ppm and H2O2 with a mass concentration of 10ppm added to an H2SO4 aqueous solution with a pH value of 3, and 50sccm of hydrogen is passed through; the corrosion current density of the sample measured by the electrochemical workstation at a constant potential of 0.84V (vs.SHE) is 0.14μA cm -2 Sample H was taken and the contact angle was measured by a contact angle meter to be 80°.
[0047] (4) Determination of coating durability: The change between the initial performance and the final performance before and after the accelerated durability test is small, and the stability of the precious metal coating is good.
[0048] Comparative Example 1A
[0049] The same metal bipolar plate sample with precious metal coating as in Example 1 was loaded into a fuel cell stack and assembled into an engine for performance testing. After 3000 hours of operation, the metal bipolar plate sample with precious metal coating was taken out of the stack and cut into 5x5cm 2 Samples AD of different sizes were placed in a beaker and ultrasonically cleaned for 5 minutes with ethanol to remove dust, impurities and oil stains on the coating surface. Sample A was taken and the bonding force between the precious metal coating and the metal substrate in sample A was measured by a scratch tester to be 47N. Sample B was taken and the contact resistance of the coating was measured by a contact resistance tester at a test pressure of 0.6MPa to be 1.77mΩcm 2 Take sample C, clamp it with an electrode clamp and put it into a glass electrolytic cell as the working electrode, use a platinum sheet as the auxiliary electrode, and Hg / HgSO4 as the reference electrode to form an electrochemical three-electrode test system. The electrolyte is a mixture of HF with a mass concentration of 100ppm and H2O2 with a mass concentration of 10ppm added to an H2SO4 aqueous solution with a pH value of 3, and 50sccm of hydrogen is passed through. The corrosion current density of the sample measured by the electrochemical workstation at a constant potential of 0.84V (vs.SHE) is 0.12μA cm -2 Sample D was taken and the contact angle was measured by a contact angle meter to be 81°.
[0050] For metal bipolar plate samples with precious metal coatings, the results obtained by the in-situ real operating environment evaluation method and the evaluation method provided by the present invention are similar, which confirms the reliability of the evaluation method.
[0051] Example 2
[0052] (1) Testing of initial coating performance: Cut the carbon-coated sample into 5x5 cm 2 Samples AD of different sizes were placed in a beaker and ultrasonically cleaned for 5 minutes with ethanol to remove dust, impurities and oil stains on the coating surface. Sample A was taken and the bonding force between the carbon coating and the metal substrate in sample A was measured by a scratch tester to be 38N. Sample B was taken and the contact resistance of the coating was measured by a contact resistance tester at a test pressure of 0.6MPa to be 5.6mΩcm 2 Take sample C, clamp it with an electrode clamp and put it into a glass electrolytic cell as the working electrode, use a platinum sheet as the auxiliary electrode, and Hg / HgSO4 as the reference electrode to form an electrochemical three-electrode test system. The electrolyte is a mixture of HF with a mass concentration of 100ppm and H2O2 with a mass concentration of 10ppm added to an H2SO4 aqueous solution with a pH value of 3, and 100sccm of hydrogen is passed through; the corrosion current density of the sample measured by the electrochemical workstation at a constant potential of 0.84V (vs.SHE) is 0.017μA cm -2 Sample D was taken and the contact angle was measured by a contact angle meter to be 75°.
[0053] (2) Accelerated durability test of coating: Another sample with precious metal coating was cut into 5x5cm 2 The samples EH of different sizes were placed in a beaker, and ethanol was added for ultrasonic cleaning for 5 minutes to remove dust, impurities and oil stains on the coating surface. Then, an electrochemical three-electrode test system with an electrochemical workstation was used to place the electrolyte pools (the electrolyte was the same as the previous step) containing the plate samples EH with coatings respectively into the ultrasonic pool, and the ultrasonic frequency was set to 30KHZ. The constant potential polarization test was performed at a temperature of 20°C and a potential of 0.8V for 12 hours, at a temperature range of 20°C and a potential of 1.6V for 3 hours, at a temperature range of 90°C and a potential of 0.8V for 12 hours, and at a temperature range of 90°C and a potential of 1.6V for 3 hours.
[0054] (3) Testing of coating performance at the end of the coating period: Sample E was taken and the bonding force between the carbon coating and the metal substrate in sample A was measured by a scratch tester to be 35 N. Sample F was taken and the coating contact resistance was measured by a contact resistance tester under a test pressure of 0.6 MPa to be 6.8 mΩcm 2Take sample G, clamp it with an electrode clamp and put it into a glass electrolytic cell as the working electrode, use a platinum sheet as the auxiliary electrode, and Hg / HgSO4 as the reference electrode to form an electrochemical three-electrode test system. The electrolyte is a mixture of HF with a mass concentration of 100ppm and H2O2 with a mass concentration of 10ppm added to an H2SO4 aqueous solution with a pH value of 3, and 100sccm of hydrogen is passed through; the corrosion current density of the sample measured by the electrochemical workstation at a constant potential of 0.84V (vs.SHE) is 0.029μAcm -2 Take sample H and use a contact angle meter to measure the contact angle to be 70°
[0055] (4) Determination of coating durability: The corrosion current density changes greatly before and after the accelerated durability test, and the stability of the carbon coating is poor.
[0056] Comparative Example 2A
[0057] The same metal bipolar plate sample with carbon coating as in Example 2 was loaded into a fuel cell stack and assembled into an engine for performance testing. After 3000 hours of operation, the metal bipolar plate sample with carbon coating was taken out of the stack and cut into 5x5 cm 2 Samples AD of different sizes were placed in a beaker and ultrasonically cleaned for 5 minutes with ethanol to remove dust, impurities and oil stains on the coating surface. Sample A was taken and the bonding force between the carbon coating and the metal substrate in sample A was measured by a scratch tester to be 33N. Sample B was taken and the contact resistance of the coating was measured by a contact resistance tester at a test pressure of 0.6MPa to be 6.9mΩcm 2 Take sample C, clamp it with an electrode clip and put it into a glass electrolytic cell as the working electrode, use a platinum sheet as the auxiliary electrode, and Hg / HgSO4 as the reference electrode to form an electrochemical three-electrode test system. The electrolyte is a mixture of HF with a mass concentration of 100ppm and H2O2 with a mass concentration of 10ppm added to an H2SO4 aqueous solution with a pH value of 3, and 100sccm of hydrogen is passed through. The corrosion current density of the sample measured by the electrochemical workstation at a constant potential of 0.84V (vs.SHE) is 0.03μA cm -2 Take sample D and use a contact angle meter to measure the contact angle to be 72°
[0058] For metal bipolar plate samples with carbon coating, the results obtained by the in-situ evaluation method and the evaluation method provided by the present invention are similar, which confirms the reliability of the evaluation method.
[0059] Example 3
[0060] The difference between this embodiment and embodiment 1 is that: (2) the ultrasonic frequency in the accelerated durability test of the coating is 50 KHZ. The contact angle of the sample measured by a contact angle meter is 80.5°.
[0061] Example 4
[0062] The difference between this embodiment and embodiment 1 is that: (2) the ultrasonic frequency in the accelerated durability test of the coating is 100 KHZ. The contact angle of the sample measured by a contact angle meter is 79.8°.
[0063] Example 5
[0064] The difference between this embodiment and embodiment 1 is that: (2) in the accelerated durability test of the coating: the constant potential polarization test is carried out for 12 hours at a temperature of 20°C and an ultrasonic frequency of 60KHZ with a potential of 0.8V, the constant potential polarization test is carried out for 3 hours at a temperature interval of 20°C and an ultrasonic frequency of 60KHZ with a potential of 1.6V, the constant potential polarization test is carried out for 12 hours at a temperature interval of 90°C and an ultrasonic frequency of 100KHZ with a potential of 0.8V, and the constant potential polarization test is carried out for 3 hours at a temperature interval of 90°C and an ultrasonic frequency of 100KHZ with a potential of 1.6V. The contact angle of the sample measured by a contact angle meter is 79.5°.
[0065] Example 6
[0066] The difference between this embodiment and embodiment 1 is that: (2) in the accelerated durability test of the coating: the constant potential polarization test is carried out for 12 hours at a temperature of 20°C and an ultrasonic frequency of 30KHZ with a potential of 0.8V, the constant potential polarization test is carried out for 3 hours at a temperature range of 20°C and an ultrasonic frequency of 40KHZ with a potential of 1.6V, the constant potential polarization test is carried out for 12 hours at a temperature range of 90°C and an ultrasonic frequency of 80KHZ with a potential of 0.8V, and the constant potential polarization test is carried out for 3 hours at a temperature range of 90°C and an ultrasonic frequency of 100KHZ with a potential of 1.6V. The contact angle of the sample measured by a contact angle meter is 79.6°.
[0067] Example 7
[0068] The difference between this embodiment and embodiment 1 is that the electrolyte is a mixture of 80 ppm NaF and 100 ppm H2O2 added to an aqueous H2SO4 solution with a pH value of 4 and 50 sccm hydrogen gas is passed through. The contact angle of the sample measured by a contact angle meter is 80.5°.
[0069] Example 8
[0070] The difference between this embodiment and embodiment 1 is that the electrolyte is a mixture of HF with a mass concentration of 0.01 ppm and H2O2 with a mass concentration of 0.01 ppm added to an aqueous H2SO4 solution with a pH value of 5, and 50 sccm of hydrogen is passed through. The contact angle of the sample measured by a contact angle meter is 81°.
[0071] Example 9
[0072] The difference between this embodiment and embodiment 1 is that the electrolyte is a mixture of KF with a mass concentration of 100 ppm and H2O2 with a mass concentration of 10 ppm added to an aqueous H2SO4 solution with a pH value of 3, and 50 sccm of hydrogen is passed through. The contact angle of the sample measured by a contact angle meter is 80°.
[0073] Example 10
[0074] The difference between this embodiment and embodiment 1 is that the electrolyte is a mixture of HF with a mass concentration of 100 ppm and H2O2 with a mass concentration of 10 ppm added to an aqueous H2SO4 solution with a pH value of 3, and 50 sccm of oxygen is passed through. The contact angle of the sample measured by a contact angle meter is 79.8°.
[0075] Embodiment 11
[0076] The difference between this embodiment and embodiment 1 is that the electrolyte is a mixture of HF with a mass concentration of 100 ppm and H2O2 with a mass concentration of 10 ppm added to a sodium dihydrogen phosphate aqueous solution with a pH value of 3, and 50 sccm of hydrogen is passed through. The contact angle of the sample measured by a contact angle meter is 80°.
[0077] Comparative Example 1
[0078] The experimental process and test method in this comparative example are the same as those in Example 1, except that the ultrasonic frequency in the accelerated durability test of the coating is set to 0KHZ. After the accelerated durability test, the bonding force between the precious metal coating and the metal substrate is measured to be 50N, and the contact resistance of the coating is 1.55mΩcm 2 , the corrosion current density is 0.10 μA cm -2 , the contact angle is 83°. The test results are quite different from the results after 3000h of testing in the real operating environment, which confirms the necessity of vibration operation.
[0079] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0080] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for evaluating a fuel cell metal plate coating, characterized in that: Preparing metal plate samples with coatings and collecting initial performance information of the samples; After the sample has undergone accelerated coating testing, the final performance information of the sample is collected; The final performance information is compared with the initial performance information to at least evaluate the performance of the sample, wherein the performance of the sample is selected from: bonding strength, contact resistance, corrosion current density and contact angle.
2. The method for evaluating the fuel cell metal plate coating according to claim 1, characterized in that: The coating acceleration experiment is as follows: in an electrolyte under ultrasonic conditions, the metal electrode plate sample is subjected to a simulated operating condition test of temperature cycling and potential cycling.
3. The evaluation method of fuel cell metal plate coating according to claim 2, characterized in that: The frequency of the ultrasonic condition is 30KHZ-100KHZ.
4. The method for evaluating the fuel cell metal plate coating according to claim 2, characterized in that: The electrolyte is a mixture of an acidic aqueous solution with a pH value of 3 to 5, to which a fluorine source with a mass concentration of 0.01 to 100 ppm and H2O2 with a mass concentration of 0.01 to 100 ppm are added, and hydrogen or oxygen is passed through the electrolyte.
5. The method for evaluating the fuel cell metal plate coating according to claim 4, characterized in that: The fluorine source is a fluorine-containing substance that is used to dissociate in an aqueous solution to form free fluorine.
6. The method for evaluating a fuel cell metal plate coating according to claim 1, characterized in that: The coating is selected from non-metallic coating, metal-based coating, and composite coating.
7. The method for evaluating the fuel cell metal plate coating according to claim 2, characterized in that: The simulated working condition test includes: performing a constant potential polarization test at a potential of 0.8V for 6-12 hours at a temperature range of -30°C-60°C; performing a constant potential polarization test at a potential of 1.6V for 3-6 hours at a temperature range of -30°C-60°C; performing a constant potential polarization test at a potential of 0.8V for 12-24 hours at a temperature range of 60°C-90°C; and performing a constant potential polarization test at a potential of 1.6V for 3-6 hours at a temperature range of 60°C-90°C.
8. The method for evaluating the fuel cell metal plate coating according to claim 7, characterized in that: The frequencies of the ultrasonic conditions in different sections in the simulated working condition test are different or the same.
9. An evaluation device for executing the evaluation method for a fuel cell metal plate coating according to any one of claims 1 to 8.
10. The evaluation device according to claim 9, characterized in that: It at least includes an electrolytic cell for containing electrolyte for testing and a functional device attached to the electrolytic cell. The functional device can be associated with the electrolytic cell or external, and the functional device is selected from: a power supply device, a temperature control device, and an ultrasonic device.